FANS PERCEPTIONS TOWARD THE APPLICATION OF VIDEO ASSISTANT REFEREE (VAR) IN FOOTBALL AT STADIUM KUALA LUMPUR - Radzliyana Radzuwan; Muhammad Hafizuddin Mohammad Rosdi; Aida Roha Abdul Rasid (JOURNAL INFORMATION AND TECHNOLOGY MANAGEMENT (JISTM), 2024)
The Video Assistant Referee (VAR) was introduced in association football in 2018 to assist on-field officials in making potentially game-changing decisions by analysing video evidence in real time. Despite its potential benefits, VAR runs the danger of being misunderstood by fans. Therefore, the purpose of this research is to identify the factors that influence fans positive and negative perceptions of technology utilization in football at Stadium Kuala Lumpur. A total of 452 football fans aged between 18 and above involved in this study by completing a survey questionnaire. The research instrument consisted of two sections namely Section A for the demographic profile of the respondent and Section B for fans perceptions on technology in football. There are 15 items in Section B and they were measured by using the 7 Likert-Scale ranging from 1 (strongly disagree) to 7 (strongly agree). All obtained data has been further analysed by using Statistical Package for Social Science (SPSS) version 27. Descriptive statistic was utilized to determine perception of the football fans while the inferential statistic (ANOVA) was used to compare between age groups. The findings illustrate that football fans at Stadium Kuala Lumpur showed a positive perception with eight survey items by having a mean value greater than four. There are significant differences between age groups in 10 out of 15 items. Overall, the findings were positive, with younger age groups more positive towards technology than older age groups due to their generation’s technology-driven nature. The study findings could enhance and contribute to the expansion of VAR technology’s use and its functionality across professional football leagues. Also, provides a valuable and reliable information to the football fans understanding and acceptance.